Validitas dan Reliabilitas Instrumen Penerimaan Pendekatan Pembelajaran Mendalam Pada Guru TK - Leni Puspita Dewi; Dadan Nugraha; Qonita Qonita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study was motivated by the limited availability of valid and reliable instruments for measuring kindergarten teachers’ acceptance of pedagogical deep learning, despite the important role of teacher acceptance in supporting the implementation of pedagogical innovations. The availability of a high-quality measurement instrument is essential for obtaining accurate information regarding teachers’ acceptance of pedagogical deep learning. Therefore, this study aimed to examine the validity and reliability of an instrument designed to measure kindergarten teachers’ acceptance of pedagogical deep learning through a pilot study. A quantitative approach with a pilot study design was employed. The participants consisted of 30 kindergarten teachers selected through convenience sampling based on accessibility and willingness to participate in the study. Data were collected using a five-point Likert-scale questionnaire comprising 22 items developed based on four constructs of the Technology Acceptance Model (TAM), namely perceived usefulness, perceived ease of use, attitude toward implementation, and behavioral intention to implement. Data were analyzed using item-total correlation for validity testing and Cronbach’s Alpha coefficient for reliability testing. The results indicated that all 22 items met the validity criteria, with item-total correlation coefficients exceeding the critical r-value (0.3610). Reliability analysis revealed Cronbach’s Alpha coefficients ranging from 0.600 to 0.791 across the four constructs, while the overall instrument achieved a reliability coefficient of 0.927. These findings indicate that the instrument demonstrates adequate measurement quality and is suitable for use in the main study. This study contributes to the preliminary development and validation of an instrument for measuring teachers’ acceptance of pedagogical deep learning in early childhood education settings